Identification of a novel cellobiose 2-epimerase from Acidobacteriota bacterium and its application for in-situ milk catalysis - Zeng, Qiuqian; Lyu, Xiaomei (Frontiers in Microbiology, 2025)
IntroductionCellobiose 2-epimerase (CE) catalyzes the interconversion of glucosyl and mannosyl groups at the reducing end of β-1,4-linked disaccharides. This enzyme is pivotal for converting lactose into prebiotics like epilactose, offering a potential solution for lactose-intolerant-friendly dairy products. However, current CEs are hindered by pH and thermal instability in milk processing, as their neutral-to-alkaline pH optima clash with milk’s mildly acidic conditions (pH 6.5–6.7), and their poor thermolability requires costly post-processing enzyme removal.MethodsWe identified a novel CE from the acidophilic Acidobacteriota bacterium (Acba-CE) and characterized its properties. Its enzymatic activity was assessed under varying pH and temperature conditions, including milk-processing environments.ResultsAcba-CE exhibits an acidic pH optimum (6.0), retaining 95% activity at milk pH (6.5). Notably, it undergoes rapid thermal inactivation at pasteurization temperatures, enabling complete enzyme deactivation during standard pasteurization without additional steps. In milk systems, Acba-CE achieves 28.5% lactose-to-epilactose conversion at refrigeration temperatures (10°C), demonstrating strong cold adaptability.DiscussionTo our knowledge, this is the first reported CE from the Acidobacteriota phylum, combining acidophilic activity with low-temperature adaptability. Acba-CE represents a breakthrough for in situ dairy modification, eliminating key bottlenecks in milk processing and enabling next-generation functional milk production.